Care and Solidarity in the Time of Covid-19: The Pandemic Experiences of Filipinos in the UK - Galam, Roderick (Archīum Ateneo, 2020)
Thisarticle provides a preliminary account of how the lives of UK-based Filipinos have been affected by the Covid-19 pandemic using care and solidarity as lenses to make sense of their experiences. By undertaking an intersectional analysis, it demonstrates how Filipinos’ experiences have been significantly shaped by the fact of their being migrants, which folds racism into their experiences. Alongside race/ethnicity and citizenship/migration status, their relationship with or location in the labor market has also shaped the impact of the pandemic on their lives. It concludes with a reflection on the duty of states to care for migrants. KEYWORDS: COVID-19 PANDEMIC • OFWS • CARE • SOLIDARITY • RACISM